Enacting connectivity: woodland mammal conservation practices in England & Wales - Hodgetts, T (2015)
In recent years ideas about connectivity have become increasingly influential in theories pertaining to wildlife conservation. These ideas range from concerns with spatial habitat linkages or species' movements, to the forms of connection existing between 'people' and 'nature'. This thesis is concerned with how these various forms of connectivity are enacted in wildlife conservation through varied spatial practices. Following Mol (2002), I suggest that these modes of connectivity are enacted not separately but as a multiple. Indeed, through tracing how connectivity is enacted in a series of conservation situations relating to woodland mammals in England and Wales (red squirrels, pine martens, and wild/feral boar), I suggest that these multiple spatial practices of connectivity shape the biopolitical possibilities for living with non-human life. Since the connectivity multiple is composed, following Latour (2010) I further argue that it can be recomposed. Thus, I make the normative suggestion that contemporary trends in conservation policy (towards larger-scale action, process-based objectives, and neoliberal modes of governance) might be rethought and differently articulated through a conceptual and practical approach I term revitalizing conservation. This thesis thus makes several important contributions to geographic literatures. Following a widespread (re)affirmation of nonhuman agency in social science (e.g. Latour, 2005; Callon et al, 2009; Braun & Whatmore, 2010), and particularly the agential capacities of animals (Wolch & Emel, 1998; Philo & Wilbert, 2000), it foregrounds the role of woodland mammals in enacting connectivity through developing the concept of animal mobilities. Furthermore, it engages with existing work tracing affirmative possibilities for conservation (bio)politics (Whatmore, 2002; Lulka, 2009; Hinchliffe et al, 2005; Hinchliffe, 2008; J.Lorimer, 2010, 2012, 2015), by illuminating the intersection of spatial practices of connectivity, and the potential these offer for alternative modes of 'living with' more-than-human lives.